CREATING A COMPLEX OF SIMULATORS AND EDUCATIONAL GAMES OF MATHEMATICS - Durdona Bekimmetova, (International Journal of Innovations in Engineering Research and Technology, 2023)
Information technology of education is a new methodological system that allows to consider the student not as an object of learning, but as a subject of learning, and the computer as a learning tool. The student moves to a new category, because the form of computer training is individual, independent, but is carried out according to the general methodology implemented in the curriculum. There are several types of educational programs: informational, reference, monitoring, combined. Some educational programs are able to monitor student knowledge, others include "training" elements, others help mastering new learning material, and others are designed to stimulate students' interest in the subject being studied. intended. To save the teacher's time, increase motivation, encourage students' initiative and creative thinking, as well as to bring educational activities closer to the game, simulators and game curricula that introduce students to mathematics. the goal of creating a plan was set. Allows you to check the "interesting" properties of numbers, the learned material and perform arithmetic operations during the game. The mysterious world of numbers and how these numbers are created is explained. The program allows you to implement the concept of the "zone of proximal development", known in pedagogy. During the game, the child sometimes performs "not yet completed" objective actions, because from the point of view of his development, he is already ready to perform these actions using the knowledge acquired at the everyday level.